The Future of Higher Arts Education : Possibilities to Shape a Trajectory - D’Hespeel, Ingwio; Garofalo, Irene; Gies, Stefan; Hansen, Maria; Hinnekint, Koenraad; Lehikoinen, Kai; Tuittila, Satu (FAST45, 2024)
This document presents futures scenarios and policy recommendations for higher arts education, addressing the imperative of facilitating policymaking and strategic decisions that effectively confront future challenges. Insights drawn from futures research assist in pinpointing and delineating influential factors, offering a foundation of reliable data. This publication was developed and published as part of the Erasmus+ Knowledge Alliance for Higher Art Education, Creative Industry, and Business – Futures Art School Trends 2045 (FAST45) project co-funded by the European Union’s Erasmus+ Knowledge Alliance programme.
Keywords: art education; policy programmes